A Review on Wear Behavior of Nickel-Silicon Carbide Electrodeposition Coating - Ariffin, Izzah Aqilah; Kamdi, Zakiah (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Nickel-silicon carbide (Ni-SiC) composites have been widely used as advanced materials, in various application fields, especially in high-temperature processing and abrasive treatment due to the Nickel and Silicon Carbide wear resistance, hardness, strength, and improve morphology and microstructure properties. The technique chosen in this study is electrodeposition, as it is a quick technique for the coating industry. Electrodeposition is a process driven by the electrical process of depositing any substance metallic or non-metallic on any substrate. Nickel and SiC provide excellent performance on wear and corrosion behavior. Next, the hardness and wear resistance of the composites will increase as the SiC content increased. Ni-SiC shows excellent performance, such as low density, low thermal expansion coefficient, and high wear resistance. The objective of this study is to identify the coating composition behavior of Ni and Ni-SiC. Then,  this study also conducts to determine the wear rate of Ni-SiC at high temperatures. Include the results here, as well as the conclusion on the changes of the parameter.